A genetic mouse model recapitulates immune checkpoint inhibitor-associated myocarditis and supports a mechanism-based therapeutic intervention - Wei, Spencer C.; Meijers, Wouter C.; Axelrod, Margaret L.; Anang, Nana-Ama A. S.; Screever, Elles M.; Wescott, Elizabeth C.; Johnson, Douglas B.; Whitley, Elizabeth; Lehmann, Lorenz; Courand, Pierre-Yves; Mancuso, James J.; Himmel, Lauren E.; et al. (Cancer discovery, 2021)
Immune checkpoint inhibitors (ICI) targeting CTLA4 or PD-1/PD-L1 have transformed cancer therapy but are associated with immune-related adverse events, including myocarditis. Here, we report a robust preclinical mouse model of ICI-associated myocarditis in which monoallelic loss of Ctla4 in the context of complete genetic absence of Pdcd1 leads to premature death in approximately half of mice. Premature death results from myocardial infiltration by T cells and macrophages and severe ECG abnormalities, closely recapitulating the clinical and pathologic hallmarks of ICI-associated myocarditis observed in patients. Using this model, we show that Ctla4 and Pdcd1 functionally interact in a gene dosage-dependent manner, providing a mechanism by which myocarditis arises with increased frequency in the setting of combination ICI therapy. We demonstrate that intervention with CTLA4-Ig (abatacept) is sufficient to ameliorate disease progression and additionally provide a case series of patients in which abatacept mitigates the fulminant course of ICI myocarditis. - Significance: We provide a preclinical model of ICI-associated myocarditis which recapitulates this clinical syndrome. Using this model, we demonstrate that CTLA4 and PD-1 (ICI targets) functionally interact for myocarditis development and that intervention with CTLA4-Ig (abatacept) attenuates myocarditis, providing mechanistic rationale and preclinical support for therapeutic clinical studies.See related commentary by Young and Bluestone, p. 537.This article is highlighted in the In This Issue feature, p. 521
Published online first November 30, 2020
Gesehen am 30.07.2021